Studi Metafora Konseptual pada Idiom Bahasa Jepang yang mengandung Bagian Tubuh dan Bermakna Emosi - Nadhira Shafa Ghassani; Akhmad Saifudin (Universitas Dian Nuswantoro, 2020)
Kanyouku is used to express human emotions. This study discusses the mapping of the meaning of Japanese idiom related to emotions in human cognition by using Knowles and Moon’s metaphor theory and conceptual metaphor theory by Lakoff and Johnson. The study utilizes 28 idioms that related to human basic emotions such as anger, happiness, sadness, fear, love, shame, pride, and surprise. These basic emotions are obtained from Goo Jiten online Japanese dictionary. The results show that human cognition viewing emotion concept as an entity and representing emotions into human body. In Japanese people’s cognition, anger represented as belly, chest, and head; fear represented as tongue, heart, and foot; happiness represented as cheek, chest, and heart; sadness represented as shoulder, chest, and heart; love represented as eye and heart; pride represented as chest; shame represented as face and cheek; and surprise represented as eye, tongue, and heart. Human cognition represented emotion concept as human body to measure the level of emotion. This study mapped the emotion concepts as a concrete entity: the entity as fluid in a container or entity as parts of body. Keywords: Cognitive Linguistic, Conceptual Metaphor, Image Scheme, Idiom, Emotion